Comparative evaluation of slide agglutination and Widal tube agglutination test in detecting enteric fever among patients attending a tertiary care hospital in North India - Jahan, Noor; Khatoon, Razia; A, Amrita; Mehrotra, Sudhir; Kumar, Swatantra (International Journal of Research in Medical Sciences, 2016)
Background: Enteric fever is a major public health problem with significant morbidity and mortality in developing countries. Although, isolation of causative organism from blood is the standard laboratory method, but due to frequent use of self-medication by patients, and its long turnaround time, it is seldom used, and enteric fever is usually diagnosed by using serological methods. Widal tube agglutination test is the standard serological test used, which is now a days replaced by slide agglutination test due to its convenience and rapidity. The present study was done to comparatively evaluate the slide agglutination and Widal tube agglutination test in detecting enteric fever. Methods: A hospital based cross-sectional study was done from January to June 2016. A total of 117 patients with clinical presentation suggestive of enteric fever were included in the study whose venous blood was collected and serum was tested by both slide agglutination and Widal tube agglutination test. Results: Out of 117 patients, slide agglutination test showed positive results in 39 (33.3%) samples, whereas, Widal tube agglutination test showed positive results in 23 (19.7%) samples only. The slide test had a sensitivity of 91.3%, specificity of 80.9%, positive predictive value of 53.8% and negative predictive value of 97.4% as compared to Widal tube agglutination test. Conclusions: Due to high false positivity shown by slide test, it is suggested that serological diagnosis should not be made solely on the basis of slide test rather its results should be confirmed by using Widal tube agglutination test.